Simple Autonomous Security System Based On Arduino UNO Platform and Fingerprint Scanner Module: A Study Case - Rusyn, Volodymyr; Subbotin, Sergey; Sambas, Aceng (CEUR-WS, 2021)
In this paper, we presented a simple autonomous security system. This security system based on the Arduino Uno and fingerprint scanner module. The Arduino was connected to a computer through the USB port and programmed using a language similar to C++. Programming code (sketch) was uploaded into Arduino using program software ArduinoIDE. Connection scheme and experimental results are presented and can be used for education.
Keywords: Fingerprint scanner; security system; Arduino